PENGARUH PERUBAHAN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Setyaningsih Sri Utami, Anjar Budi Utami, Edi Wibowo & (Universitas Slamet Riyadi, 2017)
PT Bank Tabungan Negara (Persero) Tbk is now one of the State OwnedEnterprises (SOEs) that have been listed on the Stock Exchange in Indonesia arerequired to carry out organizational changes in order to improve organizationalperformance. The purpose of this study was to analyze the significance of the effect oforganizational change, organizational culture and job satisfaction to employeeperformance. Analyze the effect of organizational change and organizational culture onemployee performance moderated job satisfaction. This study uses survey method, thetype of data used quantitative and qualitative data, the data source used primary dataand secondary data. The population in this study were all all employees of PT BankTabungan Negara (Persero) Tbk Branch Solo as many as 199 employees. The number ofsamples in this study as many as 53 employees, the sampling technique usingproportional cluster random sampling. Data collection methods used: questionnaire,observation and documentation. Data analysis technique used to test the validity,reliability test, classic assumption test, multiple linear regression analysis, t-test, F,coefficient determination and test the absolute difference. In conclusion: There was asignificant effect of organizational change, cultural organization and job satisfaction toemployee performance at PT Bank Tabungan Negara (Persero) Tbk Branch Office Solo.Job satisfaction moderate the effect of organizational change and organizational cultureon employee performance at PT Bank Tabungan Negara (Persero) Tbk Branch OfficeSolo.Keywords: organizational change, organizational culture, job satisfaction, employeeperformance.